Performance improvement in distribution network with distributed generation / Siti Rafidah Abdul Rahim - Abdul Rahim, Siti Rafidah (2006)
Recent years, the number of distributed generation (DG) installed in distribution system has been increasing in many parts of the world. Depending on their operating characteristics and locations, distributed generation could significantly affect the voltage profile, network losses and fault level in a distribution system. This thesis describes the study of installation of distributed generation (DG) in distribution system in order on improve the system performance in terms of voltage levels, losses and system efficiency. The study involves the development of new technique for determining optimal allocation and sizing of the DG in order to minimize the losses and improves the voltage in a distribution level. Sensitivity indices based on voltage stability improvement with respect to change in injected active and reactive power at a load bus were derived and used to identify the suitable location for the distributed generation. In order to determine the optimal output of the distributed generation, an evolutionary programming optimization technique was developed with an objective to minimize the distribution losses while satisfying the voltage constraint in the system. The proposed technique was tested on 69-bus and 33-bus distribution systems and the result shown a significant reduction in distribution losses and voltage profile improvement in the system. The proposed technique was developed using the MATLAB programming software. A comparative study has also shown that distributed generation is capable of providing better voltage improvement and loss minimization than those obtained from the installation of compensating capacitor.